2017
DOI: 10.1186/s12870-017-1020-8
|View full text |Cite
|
Sign up to set email alerts
|

An integrated RNAseq-1H NMR metabolomics approach to understand soybean primary metabolism regulation in response to Rhizoctonia foliar blight disease

Abstract: Background Rhizoctonia solani AG1-IA is a devastating phytopathogen causing Rhizoctonia foliar blight (RFB) of soybean worldwide with yield losses reaching 60%. Plant defense mechanisms are complex and information from different metabolic pathways is required to thoroughly understand plant defense regulation and function. Combining information from different “omics” levels such as transcriptomics, metabolomics, and proteomics is required to gain insights into plant metabolism and its regulation. As such, we st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 82 publications
3
54
0
Order By: Relevance
“…Endurance‐based strategies are postulated to be effective against necrotrophs; however, they require great amounts of metabolic energy. Consistently, a strong depletion of Glu and GABA levels was recorded in soybean leaves infected with the necrotroph Rhizoctonia solani (Copley et al, ). Endurance strategies would likely need to be supplied with substrates coming from distal, healthy areas of the plant (Seifi, Van Bockhaven, et al, ).…”
Section: A Molecular Swiss Knife: Gaba Functions In Relation To Pathomentioning
confidence: 53%
See 1 more Smart Citation
“…Endurance‐based strategies are postulated to be effective against necrotrophs; however, they require great amounts of metabolic energy. Consistently, a strong depletion of Glu and GABA levels was recorded in soybean leaves infected with the necrotroph Rhizoctonia solani (Copley et al, ). Endurance strategies would likely need to be supplied with substrates coming from distal, healthy areas of the plant (Seifi, Van Bockhaven, et al, ).…”
Section: A Molecular Swiss Knife: Gaba Functions In Relation To Pathomentioning
confidence: 53%
“…Moreover, GAD is known to be activated following cytosol acidification (Shelp et al, ; Snedden et al, ). In fact, recognition of pathogens such as bacteria and fungi was proven to trigger GABA accumulation in several plant species, such as bean ( Phaseolus vulgaris L.), tomato ( Solanum lycopersicon L.) and soybean ( Glycine max L.) (Copley, Aliferis, Kliebenstein, & Jabaji, ; O'Leary et al, ; Wang et al, ) (Table ). The accumulated GABA is presumed to be transported to the mitochondria, where it undergoes deamination via GABA transaminase (GABAT) to succinic semialdehyde (SSA) (Shelp & Zarei, ).…”
Section: Mechanisms Triggering Gaba Accumulation During Biotic Stressmentioning
confidence: 99%
“…The use of RNA-seq has provided substantial insights into plant-pathogen interactions; however, only recently have studies begun to examine the global transcriptome responses of phytopathogens such as Rhizoctonia solani while infecting host plants [ 12 , 13 ]. Although RNA-seq can provide information on both the host and pathogen, previous studies have reported that such studies provide few reads and therefore little information on the pathogen responses [ 41 , 44 , 45 ]. As such, a method using nitrocellulose membranes to obtain an in-depth and thus highly informative study of R .…”
Section: Discussionmentioning
confidence: 99%
“…Transcript levels were quantified in three biological replicates per treatment and significant differences determined using analysis of variance (ANOVA) and student’s t test at the 95% significance level using R statistics software. Fold change differences ≤ -1.5 or ≥ 1.5 with P <0.05 were used for qRT-PCR rather than ≤ -3 or ≥ 3 due to the differences in methods of normalization between RNA-seq and qRT-PCR [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…OnPLS is the multiblock extension of the O2PLS algorithm, and the method is often used for integrating –omics data . O2PLS is based on analysis of the covariance matrix of two blocks, X1tX2.…”
Section: Data Fusion Methodsmentioning
confidence: 99%